2005
DOI: 10.1158/1535-7163.mct-05-0036
|View full text |Cite
|
Sign up to set email alerts
|

Gene therapy withE2F-1up-regulates the protein kinase PKR and inhibits growth of leiomyosarcomain vivo

Abstract: Overexpression of the transcription factor E2F-1 induces apoptosis in a variety of carcinoma cells and inactivates murine double minute protein 2, a factor associated with poor prognosis in soft tissue sarcomas. We have shown previously that the double-stranded RNA-activated protein kinase PKR plays an important role in mediating this apoptotic response in carcinoma cells to E2F-1. We sought to evaluate the potential of E2F-1 gene therapy in soft tissue sarcomas and to study the involvement of PKR in the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
(14 reference statements)
2
15
0
Order By: Relevance
“…In concordance with previous reports from non-prostate tumor models (13, 14), Ad-E2F1 injection alone reduced TV in orthotopic LNCaP tumors (Tables 1 and 2). …”
Section: Discussionsupporting
confidence: 92%
“…In concordance with previous reports from non-prostate tumor models (13, 14), Ad-E2F1 injection alone reduced TV in orthotopic LNCaP tumors (Tables 1 and 2). …”
Section: Discussionsupporting
confidence: 92%
“…Concurring with these results, E2F-1 overexpression induces PKR expression and autophosphorylation (Fig. 5), leading to phosphorylation of its downstream target eIF-2␣ and to apoptotic cell death in a variety of carcinoma cells (367,369). PKR can interact with STAT1 to regulate its DNA-binding activity (381); PKR also can interact with and activate STAT3 in response to the cell growth regulator factor PDGF (73).…”
Section: Pkr Regulation Of Transcription Factorsmentioning
confidence: 76%
“…Preclinical studies using overexpression of E2F1 have shown the induction of apoptosis in several types of human cancer cells, including glioma, melanoma, pancreatic, colon and non-small-cell lung cancers. 9,[37][38][39][40] In all cases, the adenoviral expression of E2F1 resulted in growth suppression, 41,42 suggesting that modulation of E2F1-induced apoptosis could be a promising therapeutic approach in several types of cancer. It has been shown that E2F1 sensitizes cells to chemotherapeutic agents 43 and that the combination of E2F1 gene therapy and chemotherapy produces a synergistic effect on melanoma cell apoptosis.…”
Section: Resultsmentioning
confidence: 99%